Corrective Training for the First Years of Classical Ballet at the Hungarian Dance University - Fanni Bogáti; Judit Benedek; Melinda Szitt (Tánc és Nevelés, 2023)
At the beginning of the academic year, all students newly admitted to the classical ballet dancer training course at The Hungarian Dance University are assessed at the child development and therapy center called Bárányfelhő. After the assessment of their motor and neurodevelopment, children can have special skills development training integrated into their curriculum. Among the 33 children assessed in September 2020, significant differences were found in regard to cross-body movements as well as the independent use and coordination of the upper and lower extremities. In the seventh month following the evaluation, the ballet masters of these classes reported development in the children’s concentration, coordination, balance, and attention, as well as the independent use of the limbs and proprioception. The skills development training has a compound effect: as students` coordination skills improve, they experience more success and, as a result, become more self-confident. This kind of specific skills development at the Hungarian Dance Academy not only addresses a gap in professional dancer training but is also unique among professional dancer courses.